Brd4‐Brd2 isoform switching coordinates pluripotent exit and Smad2‐dependent lineage specification. (6th June 2017) - Fernandez‐Alonso, Rosalia; Davidson, Lindsay; Hukelmann, Jens; Zengerle, Michael; Prescott, Alan R; Lamond, Angus; Ciulli, Alessio; Sapkota, Gopal P; Findlay, Greg M
Abstract: Pluripotent stem cells (PSCs) hold great clinical potential, as they possess the capacity to differentiate into fully specialised tissues such as pancreas, liver, neurons and cardiac muscle. However, the molecular mechanisms that coordinate pluripotent exit with lineage specification remain poorly understood. To address this question, we perform a small molecule screen to systematically identify novel regulators of the Smad2 signalling network, a key determinant of PSC fate. We reveal an essential function for BET family bromodomain proteins in Smad2 activation, distinct from the role of Brd4 in pluripotency maintenance. Mechanistically, BET proteins specifically engage Nodal gene regulatory elements (NREs) to promote Nodal signalling and Smad2 developmental responses. In pluripotent cells, Brd2‐Brd4 occupy NREs, but only Brd4 is required for pluripotency gene expression. Brd4 downregulation facilitates pluripotent exit and drives enhanced Brd2 NRE occupancy, thereby unveiling a specific function for Brd2 in differentiative Nodal‐Smad2 signalling. Therefore, distinct BET functionalities and Brd4‐Brd2 isoform switching at NREs coordinate pluripotent exit with lineage specification. Synopsis: BET bromodomain proteins are key regulators of Nodal‐Smad2 signalling during mesendoderm differentiation of mESCs. In this system distinct functionalities of the BET family proteins Brd2 and Brd4 coordinate the exit from pluripotency with mesendoderm specification. BET bromodomain activity regulates the Nodal‐Smad2 pathway and mesendoderm specification. Brd2‐Brd4 recruitment controls Nodal expression and Smad2 signalling in differentiating mESCs. Distinct Brd2‐Brd4 roles ensure that pluripotent exit coordinates with mesendoderm specification. Brd2 is a novel specific regulator of Nodal‐Smad2 signalling and mesendoderm differentiation. Abstract : BET bromodomain proteins are key regulators of Nodal‐Smad2 signalling during mesendoderm differentiation of mESCs. In this system distinct functionalities of the BET family proteins Brd2 and Brd4 coordinate the exit from pluripotency with mesendoderm specification.